Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Review: 36



Work Step by Step

$\dfrac{2}{x-3}-\dfrac{4}{x-1}$ Evaluate the substraction of the two rational expressions: $\dfrac{2}{x-3}-\dfrac{4}{x-1}=\dfrac{2(x-1)-4(x-3)}{(x-3)(x-1)}=\dfrac{2x-2-4x+12}{(x-3)(x-1)}=...$ $...=\dfrac{-2x+10}{(x-3)(x-1)}=...$ Take out common factor $-2$ from the numerator to provide a more simplified answer: $...=-\dfrac{2(x-5)}{(x-3)(x-1)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.